Dipeptidyl peptidase IV inhibitors: Therapeutic potential in nonalcoholic fatty liver disease - (:unkn) unknown (INT SCIENTIFIC LITERATURE, INC, 2009)
Nonalcoholic fatty liver disease is the most common chronic liver disease in industrialized countries and is considered the hepatic manisfestation of metabolic syndrome. Apart from correction of underlying metabolic abnormalities, restriction of calorie intake, and physical exercise, no drugs have been licensed for the treatment of nonalcoholic fatty liver disease. Of note, reduced calorie intake and exercise with resultant weight loss may lead to a reduction in liver fat content, but no studies have shown long-term benefits of this. Dipeptidyl peptidase IV inhibitors are promising new oral drugs for the treatment of type 2 diabetes. Here, we hypothesize that dipeptidyl peptidase IV inhibitors can reduce fat infiltration in the liver and thus be a potential treatment for non-alcoholic fatty liver disease. There are 3 lines of evidence supporting this hypothesis. First, dipeptidyl peptides IV inhibitors are known to improve insulin resistance, a key metabolic abnormality encountered by patients with nonalcoholic fatty liver disease. Second, patients with nonalcoholic steatohepatitis have increased dipeptidyl peptidase IV activity, which has been found to correlate positively with the histopathologic grade and degree of liver steatosis. Finally, data from experimental studies suggest that dipeptidyl peptidase IV inhibitors can reduce liver inflammation and steatosis. In light of these findings, we propose that pharmacologic inhibition of dipeptidyl peptidase IV may provide a new therapeutic option for slowing the progression of nonalcoholic fatty liver disease. Future research is expected to support the efficacy and tolerability of dipeptidyl peptidase IV modulation in early liver steatosis.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; dipeptidyl peptidase inhibitors; treatment; GLUCAGON-LIKE PEPTIDE-1; DPP-4 INHIBITORS; RECEPTOR AGONIST; CONTROLLED-TRIAL; INCRETIN SYSTEM; METFORMIN; STEATOHEPATITIS; ROSIGLITAZONE; VILDAGLIPTIN; SITAGLIPTIN